HIDROLOGICAL SIMULATION OF THE RIVERS’ FLOOD CONTROL IN SUBDISTRIC WONOKERTO IN PEKALONGAN REGENCY - Bayu Purnama Fitra; Slamet Imam Wahyudi; Moh Faiqun Ni’am (UNISSULA Semarang, 2018)
Abstract: Flooding problem still become serious problem in subdistrict Wonokerto of Pekalongan regency. There are six rivers that have the potential caused flooding in setelment area. In this research, the researcher wanted to do hydrological simulation at six rivers in Wonokerto. The hydrological simulation is done by calculating the inflow in the river in the form of flood discharge hydrograph design with nakayasu method, and evaluate the capacity of river catchment to flood discharge. Based the results research on six rivers, it is known that the river capacity is not able to accommodate the flood discharge when enters the river. The River water are also known unable to flow by gravity caused of rob dikes that isolated the river water to flow into the sea, therefore to prevent overflow in the river needs and to prevent overflow and to control the river water level a pumping in rivers.Keywords: Hydrological Simulation, River Flood Control, Storage Evaluation, Pumping